2017
DOI: 10.1016/j.amjsurg.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a comprehensive mental skills curriculum in enhancing surgical performance: Results of a randomized controlled trial

Abstract: Introduction-We hypothesized that the implementation of a novel mental skills curriculum (MSC) during laparoscopic simulator training would improve mental skills and performance, and decrease stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 29 publications
(39 reference statements)
1
44
0
2
Order By: Relevance
“…El cirujano que realiza EM utiliza su mente como un simulador (17,18), que le permite mejorar su desempeño en diferentes situaciones y contextos:…”
Section: Em En Cirugíaunclassified
See 1 more Smart Citation
“…El cirujano que realiza EM utiliza su mente como un simulador (17,18), que le permite mejorar su desempeño en diferentes situaciones y contextos:…”
Section: Em En Cirugíaunclassified
“…• Manejo del estrés e incertidumbre El EM propicia el fortalecimiento de las habilidades mentales y facilita el adecuado control del ambiente quirúrgico, creando un esquema mental claro que mejora la toma de decisiones (6,17).…”
Section: Em En Cirugíaunclassified
“…Although physical practice is essential for the mastery of complex motor skills, MP has been found to be a promising adjunct to facilitate skill learning and performance (Taktek, 2004) [3]. This technique has been employed successfully in teaching and rehearsing complex psychomotor tasks in several domains, including sports (Feltz DL, 1983;Martin K., 1999) [4], [5]; music education [2], [6] and recently, in perceptuo-motor professional skills such as in surgery (Anton NE, et al, 2017) [7] and nursing (Bachman K., 1990) [8]. Recent upsurge in fundamental and behavioural science have established e cacy of MP and has resulted in widespread use of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…10 Accordingly, we sought to ameliorate this dearth in surgical education by 3 developing a novel and comprehensive mental skills curriculum (MSC) and have implemented it with diverse learners. [11][12][13][14] Initially, our group implemented our MSC with surgical novices in a pilot study of its effectiveness during their laparoscopic skills training. 11 From baseline to post-test, we observed significant increases in novices' use of mental skills (i.e., overall use of mental skills in practice and performance settings, attention, and mental imagery) and significantly increased laparoscopic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized-controlled trial with surgical novices, we implemented our MSC with participants concurrently with laparoscopic skills training, whereas the control group only participated in laparoscopic skills training. 13 Participants completed two transfer tests of laparoscopic skill, an initial test immediately after training, and a retention test of skill after two to three months of no training. We observed that MSC-trained novices displayed significantly enhanced surgical skill retention compared to controls.…”
Section: Introductionmentioning
confidence: 99%